Copper Oxide Nanostructures; Syntheses and Characterization - ALgawi, Sariya D AL (Al-Nahrain Journal of Science, 2018)
Copper oxide (CuO) nanoparticles are synthesized by pulse laser ablation (Nd:YAG, λ=1064nm,) of cupper (Cu) in pure water (DDDW). The synthesized nanomaterial is characterized with UV-Visible spectroscopy; atomic force microscopy AFM, in combination with FTIR.AFM image shows that the CuO are spherical in shape with average diameter 51 nm and FTIR spectrum confirm the formation of CuO nanoparticles. The UV–vis spectrum of the colloidal nanoparticles shows maximum absorbance around the UV region at ~270nm and in Vis region at~600nm, indicating the formation of CuO nanoparticles with a direct bandgap energy of~ 3.2eV.